Tantangan Konflik Perbatasan Thailand-Kamboja Bagi Stabilitas ASEAN - Sandy Nur Ikfal Raharjo (Jurnal Kajian Wilayah, 2013)
ASEAN (Association of Southeast Asian Nations) as one of the worlds leading regional organization is moving forward to develop a more solid entity and to take a bigger role in the world. This rapid development is represented in the well-planned ASEAN Community 2015 and in the optimistic prediction of ASEANs key role in the Asian Century 2050. Nevertheless, regional stability as the main requirement to realize those development still have to face challenges, particularly dispute and conflict that exist among its member countries. This qualitative research will describe Thai-Cambodia border conflict and its potential impact toward regional stability. Besides, analysis on ASEANs effort to deal with these challenges will also be conducted.Keywords: ASEAN, Cambodia, conflict, dispute, and Thailand.